Unilesional self‐limited Langerhans cell histiocytosis: a case report and review of the literature. (3rd April 2013) - Wheller, Laura; Carman, Nicholas; Butler, Greg
<x xml:space="preserve">Abstract</x> Self‐limited Langerhans cell histiocytosis (LCH) represents a rare, congenital, cutaneous form of LCH associated with a good prognosis. Only 35 cases of solitary lesion self‐limited LCH have been reported. Herein, we present an additional case in a 3‐month‐old boy who presented with an isolated pigmented nodule on his left posterior shoulder, which had been present since birth. Punch biopsy showed histopathologic features of LCH with positive CD1a and CD68 stains. Further examination and investigation showed no features of systemic involvement. The lesion spontaneously resolved within 2 months, and there has been no evidence of recurrence on follow up. As several cases of recurrence and complications have been reported in self‐limited LCH, we emphasize the need for long‐term, and perhaps indefinite, follow up for symptoms and signs associated with LCH in these patients.